Correlation between reduction in macular vessel density and frequency of intravitreal ranibizumab for macular oedema in eyes with branch retinal vein occlusion. Issue 1 (15th March 2018) - Hasegawa, Taiji; Murakawa, Sakura; Maruko, Ichiro; Kogure-Katakura, Akiko; Iida, Tomohiro
Abstract : Aim: To determine whether there is a significant correlation between the reduction in macular vessel density and the recurrence of macular oedema in eyes with branch retinal vein occlusion (BRVO). Methods: We reviewed the medical records of 27 eyes with macular oedema associated with BRVO. All eyes had received pro re nata intravitreal ranibizumab (IVR) injection. A reinjection of ranibizumab was performed when the central foveal thickness was ≥300 µm. At 12 months, patients without additional IVR for the last 4 months were placed in the resolved group, otherwise they were placed in the recurrence group. The macular vessel density in 3×3 mm area centred on the fovea was determined by optical coherence tomography angiography. Results: At 12 months, 11 of the 27 (40.7%) eyes were placed in the resolved group and the other 16 (59.3%) eyes were placed in the recurrence group. The mean macular vessel density reduction in the resolved group was 17.60%±7.88% and that in the recurrence group was 8.12%±7.48% (P=0.0042). The mean number of IVR injections in the resolved group was 2.1±1.1 and that in the recurrence group was 5.1±1.2 (P<0.0001). In all eyes, multivariate analysis showed that the reduction in macular vessel density was significantly and negatively correlated with the number of IVR injections (β=−0.6746, P=0.0028). Conclusions: A reduction in the macular vessel density was significantly correlated with the number of recurrences of macular oedema associated with BRVO.